The addiction progress notes planner - Berghuis, David J.; Jongsma, Arthur E., Jr., 1943- (Practice planners., 2015)
"Save hours of time-consuming paperwork. The Addiction Progress Notes Planner, Fifth Edition provides prewritten session and patient presentation descriptions for each behavioral problem in the Addiction Treatment Planner, Fifth Edition. The prewritten progress notes can be easily and quickly adapted to fit a particular client need or treatment situation. Saves you hours of time-consuming paperwork, yet offers the freedom to develop customized progress notes Organized around 44 behaviorally based presenting problems including depression, gambling, nicotine abuse/dependence, chronic pain, and eating disorders Features over 1,000 prewritten progress notes summarizing patient presentation, themes of session, and treatment delivered Provides an array of treatment approaches that correspond with the behavioral problems and DSM-5 diagnostic categories in The Addiction Treatment Planner, Fifth Edition Offers sample progress notes that conform to the latest ASAM guidelines and meet the requirements of most third-party payors and accrediting agencies, including CARF, TJC, COA, and the NCQA Incorporates new progress notes language consistent with Evidence-Based Treatment Interventions "--